2013
DOI: 10.1186/1471-2407-13-425
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor alpha/beta ratio and estrogen receptor beta as predictors of endocrine therapy responsiveness–a randomized neoadjuvant trial comparison between anastrozole and tamoxifen for the treatment of postmenopausal breast cancer

Abstract: BackgroundThe role of estrogen receptor beta (ER-β) in breast cancer (BC) remains unclear. Some studies have suggested that ER-β may oppose the actions of estrogen receptor alpha (ER-α), and clinical evidence has indicated that the loss of ER-β expression is associated with a poor prognosis and resistance to endocrine therapy. The objective of the present study was to determine the role of ER-β and the ER-α/ER-β ratio in predicting the response to endocrine therapy and whether different regimens have any effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 55 publications
(81 reference statements)
0
42
0
1
Order By: Relevance
“…Several mechanisms such as the coactivator-corepressor ratio and tissue-selective modulation of signaling pathways that have been established as mechanisms for the tissue-selectivity of SERMs are also applicable to the SARMs (50,51). The tissue-selective expression of ER-isoforms, (ER-α and ER-β), that often have distinct responses to ligand and thereby provide tissue-selective modulation of ER function by SERMs is unique to SERMs (52). A variety of other molecular mechanisms likely contribute to the observed tissue-selectivity of SARMs.…”
Section: Mechanisms For Sarm Tissue-selectivitymentioning
confidence: 99%
“…Several mechanisms such as the coactivator-corepressor ratio and tissue-selective modulation of signaling pathways that have been established as mechanisms for the tissue-selectivity of SERMs are also applicable to the SARMs (50,51). The tissue-selective expression of ER-isoforms, (ER-α and ER-β), that often have distinct responses to ligand and thereby provide tissue-selective modulation of ER function by SERMs is unique to SERMs (52). A variety of other molecular mechanisms likely contribute to the observed tissue-selectivity of SARMs.…”
Section: Mechanisms For Sarm Tissue-selectivitymentioning
confidence: 99%
“…The exact role of ER is not clear, however studies have shown that tamoxifen can bind ER and that tamoxifen-bound ER can activate AP1 regulated genes, possibly by altering the balance of associated coactivators and corepressors at the promoter site [135,136]. Indeed, increased ER expression has been reported in tamoxifen resistant breast cancers and data from a recent study suggested that the ratio of ER to ER may be important in predicting response to tamoxifen and anastrozole in the neoadjuvant setting [137,138].…”
Section: Er-independentmentioning
confidence: 99%
“…Loss of ERα and ERβ, and increased ERα to ERβ ratio, as observed in OW and DIO mice, have each been linked with poor breast cancer prognosis in clinical studies (38, 39). Our finding that the ERα to ERβ ratio, a prognostic indicator in breast cancer, can be manipulated by energy balance modulation has not, to our knowledge, been previously reported.…”
Section: Discussionmentioning
confidence: 99%